Estimation of Reference Evapotranspiration using the FAO Penman-Monteith Method for Climatic Conditions of Poland - Łabędzki, Leszek; Kanecka-Geszke, Ewa; Bak, Bogdan; Slowinska, Sandra (IntechOpen, 2011)
None